The Diagnostic Significance of Coapplying a Rabeprazole Test with the SF-36 for Gastroesophageal Reflux Disease. (28th February 2013) - Chen, Ying; Wang, Feng; Jiang, Yuanxi; Wang, Chen; Yao, Liwen; Wu, Ping; Tong, Yili; Sun, Huihui; Xu, Shuchang
Abstract : Gastroesophageal reflux disease is a diversity disease that affects life quality of people in the world. Due to the complicated pathogenesis and variations in clinical manifestations, there is still no true gold standard for GERD diagnosis, and it is still difficult to diagnose this disease in some patients. The proton pump inhibitor's diagnostic test (the PPI test) is noninvasive, of low cost, tied to treatment, and widely accepted. Our aim is to evaluate the diagnostic significance of coapplying a rabeprazole test with the SF-36 for GERD in this study. Our study shows that the SF-36 in combination with the rabeprazole test can screen GERD patients and increase the sensitivity and specificity of GERD diagnosis through reference to the change in SF-36 score before and after the treatment (65 in the trial).